2016
DOI: 10.1093/cercor/bhv336
|View full text |Cite
|
Sign up to set email alerts
|

Gradient COUP-TFI Expression Is Required for Functional Organization of the Hippocampal Septo-Temporal Longitudinal Axis

Abstract: The hippocampus (HP), a medial cortical structure, is subdivided into a distinct dorsal (septal) and ventral (temporal) portion, which is separated by an intermediate region lying on a longitudinal curvature. While the dorsal portion is more dedicated to spatial navigation and memory, the most ventral part processes emotional information. Genetic factors expressed in gradient during development seem to control the size and correct positioning of the HP along its longitudinal axis; however, their roles in regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 63 publications
12
53
0
1
Order By: Relevance
“…2E,E′,I), in which its septal region is 51% smaller than the control (Fig. S1A), in line with the selective hippocampal reduction we have previously described (Flore et al, 2017). By P7, the total volume of the mutant DG is decreased to 68% of its normal size ( Fig.…”
Section: Coup-tfi Inactivation In Progenitors Results In Progressive supporting
confidence: 88%
See 3 more Smart Citations
“…2E,E′,I), in which its septal region is 51% smaller than the control (Fig. S1A), in line with the selective hippocampal reduction we have previously described (Flore et al, 2017). By P7, the total volume of the mutant DG is decreased to 68% of its normal size ( Fig.…”
Section: Coup-tfi Inactivation In Progenitors Results In Progressive supporting
confidence: 88%
“…In this study, we unravel for the first time a key function of the transcriptional regulator COUP-TFI in DG development. We have previously shown that COUP-TFI is required for proper growth and morphogenesis of the hippocampal septal pole and its connectivity to the entorhinal cortex (Flore et al, 2017), but the origin and mechanisms of these defects have not been elucidated. Here, we show that COUP-TFI is highly expressed in the dentate primordium and maintained in all precursors during migration and differentiation, thus representing one of the few transcription factors expressed throughout all stages of DG morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that COUP-TFI acts on the LMS population expressing SP8 and on the MMS population expressing COUP-TFII. The regulation of COUP-TFI on Sp8 expression has been well documented in the cortex (Alfano et al, 2014b;Borello et al, 2014), and control of COUP-TFI on COUP-TFII expression levels has been recently shown in the hippocampus (Flore et al, 2016). Thus, a similar mechanism in the CGE might limit the cohort of LMS SP8 + cells reaching the cortex, and compensate for the lack of COUP-TFI in the MMS, as previously proposed for the hippocampus, as both COUP-TFs have similar binding sites and could thus compete for the same target genes (Alfano et al, 2014a).…”
Section: Coup-tfi Controls the Rostral But Not The Caudal Migratory Rmentioning
confidence: 99%